DENTAL STATUS OF CHILDREN BEFORE AND AFTER PREVENTIVE MEASURES - Liubarets, S.F.; Savychuk, O.V. (World of Medicine and Biology, 2020)
The total of 117 children aged 6-12 years were examined at the Department of Pediatric and Preventive Dentistry of the Bogomolets National Medical University. Children were divided into two groups: I - persons with chronic diseases of the internal organs at the stage of compensation, II - children with risk factors for somatic diseases. The above two groups were divided into several groups, taking into account disturbances in tooth formation. Group I included children with systemic enamel hypoplasia (group 1) and children with molar incisor hypomineralization of enamel (group 2). Group II consisted of children with systemic enamel hypoplasia (group 3), children with molar incisor hypomineralization of enamel (group 4), children without disturbances in tooth formation (group 5). The efficacy of the developed and implemented set of treatment and prevention measures for prevention of complications in children with dental disorders is confirmed by positive changes in dental status (improvement of oral hygiene, reducing the severity of inflammation in periodontal tissues).
Keywords: disturbances in tooth formation; systemic enamel hypoplasia; molar incisal hypomineralization of enamel; caries; periodontium; prevention; children